(untitled) (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2023)
Breastfeeding should be a pleasant experience for both mother and baby because there are many benefits of breastfeeding, including exclusive breastfeeding. But sometimes, various problems arise when breastfeeding both the mother and the baby, which complicates the process. The breastfeeding problems that may be experienced by the mother and the baby are; The problem is because the milk production is less so it does not provide exclusive breastfeeding. The purpose of this research is to find out "The Effect of Giving Marmet Techniques on the Smoothness of Breastfeeding for Postpartum Mothers at the Gaji Health Center in Tuban Regency". The research design used a pre-experimental type of design using a statistical test with a paired T test with a p value <0.05. The population of all postpartum women in the working area of ​​the Gaji Health Center in February 2023 was 30 people. The results of the study based on the identification of the smoothness of breastfeeding before the guinea pig technique was carried out on postpartum mothers at the Gaji Health Center in Tuban Regency were 11 respondents (36.7%). There were 27 respondents (90%) who identified the fluency of breastfeeding after using the guinea pig technique for postpartum mothers at the Gaji Health Center in Tuban Regency. Based on bivariate analysis using the Paired T Test, it was found that the effect of the marmet technique on the smooth production of breast milk for post partum mothers at the Salary Health Center had a p value of 0.000 <0.05. It was concluded that there was an effect of the marmet technique on the smooth expulsion of breast milk in post partum mothers at the Salary Health Center at the Gaji 2023 Health Center, therefore health workers, especially midwives, are expected that the marmet technique needs to be applied to every postpartum mother, whether breastfeeding is smooth or not smooth so that the mother can provide maximum breastfeeding Keywords: Marmet Techniques, Fluency, Breastfeeding, Post partum